Drip Fertigation for Higher Crop Production IFFCO initiative - Singh, Tarunendu; Singh, A P; Singh, Madhu; Pal, Ved; Kaore, S V (Indian Farming, 2017)
Precision farming is going to become one of the integral components of modern farming practices since the input economy and concern for environment as well as control on agriculture can be exercised to an extent by this technology. Drip-fertigation is one of the components of precision farming. With the changing agricultural scenario and shift towards remunerative agriculture application of this technology will expand. There has been an opinion to cover most of the water guzzling crops such as sugarcane under drip and fertigation in states like Maharashtra and Karnataka. Similarly, cotton and even rice and wheat area may shift towards this technology in future. Therefore, keeping in view the benefit of drip fertigation steps need to be taken for its integration in different cropping systems.